Re-assessment of two metallographically examined early medieval swords from Staré Město (Uherské Hradiště district), Czech Republic - Jiří Hošek; Jiří Košta; Luděk Galuška (UISPP Journal)
In 1990s, two early medieval swords from the Great Moravian centre of Staré Město (Czech Republic) were examined metallographically in order to describe the way of their production in details. Although both swords were very carefully analysed, both of them were misinterpreted and described as non-pattern-welded items, though both of them have a pattern-welded blade. The main reason for the misinterpretation is that the metallographers in charge believed, like many others at the time, that pattern-welded composites are only those consisting of layers of steel and soft iron. A re-assessment of these weapons is the topic of this article.